The eye and the hand: the phenomenology of perception in the graphies of portrait ands Self-portrait (Revista de Ensino em Artes, Moda e Design, 2026)
This article reports a pedagogical experience developed in the Arts curricular unit at the Federal Institute of Santa Catarina – Tubarão Campus, with first-year students from integrated technical programs in Administration and Industrial Automation. Its objective is to analyze, from the perspective of complex thought, the phenomenology of the gaze applied to portrait and self-portrait drawing practices, understood as a field of meaning production within processes of graphic authorship. The methodology is characterized by a descriptive-interpretative approach, articulating cartography (Sant'Anna, 2024)  as a guiding principle of the experience, from which four interdependent acts are structured: the first, facing oneself; the second, facing heritage; the third, facing montage; and the fourth, facing the complex image. On the theoretical level, the study mobilizes the phenomenology of perception (Merleau-Ponty, 2018), the understanding of the image as event and survival (Didi-Huberman, 2013), representation as the production of meaning (Hall, 2016), and complex thought (Morin, 2015), in order to support drawing as a relational field in which perception, image, and experience mutually implicate one another. It is argued that the phenomenology of the gaze enables the aesthetic and political formation of students by shifting drawing from a representational logic toward a field of sensitive and critical experience.
Keywords: phenomenology of the gaze; complex thought; critical appropriation; portrait and self-portrait